A floristic survey of angiosperm species occurring at three landscapes of the Central Amazon várzea, Brazil - Luize, Bruno Garcia [UNESP]; Venticinque, Eduardo Martins; Silva, Thiago Sanna Freire [UNESP]; Novo, Evlyn Marcia Leão de Moraes (Pensoft Publishers, 2015)
The Amazonian floodplains harbor highly diverse wetland forests, with angiosperms adapted to survive extreme floods and droughts. About 14% of the Amazon Basin is covered by floodplains, which are fundamental to river productivity, biogeochemical cycling and trophic flow, and have been subject to human occupation since Pre-Colombian times. The botanical knowledge about these forests is still incomplete, and current forest degradation rates are much higher than the rate of new botanical surveys. Herein we report the results of three years of botanical surveys in floodplain forests of the Central Amazon. This checklist contains 432 tree species comprising 193 genera and 57 families. The most represented families are Fabaceae, Myrtaceae, Lauraceae, Sapotaceae, Annonaceae, and Moraceae representing 53% of the identified species. This checklist also documents the occurrence of approximately 236 species that have been rarely recorded as occurring in white-water floodplain forests.
Keywords: Amazonian wetlands; Angiosperms; Brazil; Floristic survey; White-water floodplain forests